Dirección y producción del videoclip ‘Sunshine’ de la banda Alther - Pacheco Pérez, Andrea de Jesús (2023)
This project delves into the detailed production process of the music video 'Sunshine' by the band Alther, focusing on the roles of direction and production. The main objective was to capture the creative essence and unique identity of the band in a high-quality digital product, surpassing their previous works. The music video stands out for its futuristic and gamer-themed visuals, achieved through a modern and appealing visual narrative. Despite the challenge of a limited budget, constant communication with the band and the self-managed team proved crucial in achieving success. Collaboration with key professionals enabled an efficient realization of the project. This project offers promising perspectives for future audiovisual and musical productions, featuring an innovative approach to creating impactful and captivating music videos.